Ласточкино гнездо: стихи : переводы с удмуртского / Владимир Романов - Романов Владимир Васильевич (Удмуртия, 2004)
Экземпляры: ХР (20180522) / Инвентарный номер: 38913 / Цена: 10 / Сис.шифр: С(Удм) / Авт.знак: Р 69 / ГРНТИ: 17.82.10 / ББК: С(Удм)